STRATEGI MENINGKATKAN KEMAMPUAN PUSTAKAWAN DALAM MELAYANI PEMUSTAKA DI PERPUSTAKAAN INSTITUT AGAMA ISLAM NEGERI PONTIANAK - Mitania, Melda; Sahidi, Sahidi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study discusses strategies to improve the ability of librarians in serving users at the IAIN Pontianak Library. The purpose of the study was to determine the library strategy of IAIN Pontianak to improve the ability of librarians to serve users, types of services and library constraints in implementing strategies to improve the ability of librarians. This type of research is descriptive research with a qualitative approach. The data sources of this research are the head of the library, librarians, and users. Data collection techniques through observation, interviews, and documentation. The results showed that the strategy carried out by the IAIN Pontianak library was to include librarians and library staff in librarianship training, become members of librarian organizations at both the provincial and national librarianship organizations and improve literacy education. The types of services provided by librarians to users are the behavior of librarians towards users to improve services, types of services that are not yet available, types of services that are most influential and how to deal with users who complain about services. The obstacles faced are the basic abilities of various librarians, limited funds, and the librarians have not mastered the basic applications of information systems.Keywords: Library, Strategy, type of service